ФІНАНСОВІ ІНДИКАТОРИ ВПЛИВУ ГРОШОВИХ ПЕРЕКАЗІВ ТРУДОВИХ МІГРАНТІВ НА СОЦІАЛЬНО-ЕКОНОМІЧНИЙ РОЗВИТОК ДОМОГОСПОДАРСТВ - Ясинська, Надія Альбертівна (Науковий журнал «Світ фінансів», 2018)
Ясинська Н. А. Фінансові індикатори впливу грошових переказів трудових мігрантів на соціально-економічний розвиток домогосподарств. Проаналізовано передумови й сучасний стан ринку грошових переказів трудових мігрантів в Україні. Виявлено поточні економічні проблеми домогосподарств, які визначають процеси трудової міграції. Охарактеризовано нові тенденції на міграційному ринку праці. Визначено фінансові індикатори, які здійснюють вплив на особисті рішення щодо грошових переказів трудових мігрантів в контексті соціально-економічного розвитку домогосподарств, які їх отримують. Встановлено залежність фінансової поведінки мігрантів від рівня соціально-економічного розвитку їх домогосподарств. Ясинская Н. А. Финансовые индикаторы влияния денежных переводов трудовых мигрантов на социально-экономическое развитие домохозяйств. Проанализированы предпосылки и современное состояние рынка денежных переводов трудовых мигрантов в Украину. Выявлены текущие экономические проблемы домохозяйств, которые определяют процессы трудовой миграции. Охарактеризованы новые тенденции на миграционном рынке труда. Определены финансовые индикаторы, которые оказывают влияние на личные решения относительно денежных переводов трудовых мигрантов в контексте социально-экономического развития домохозяйств, которые их получают. Выявлена зависимость финансового поведения мигрантов от уровня социально-экономического развития домохозяйств, в состав которых они входят. Yasynska N. Financial indicators of influence of remittances of labor migrants on social and economic development of household. Introduction. In the model of demographic transition and with the expansion of migration flows, the remittances of labor migrants tactically solve the problems of strengthening the socioeconomic status of households. Further studies are requiring questions of financial preconditions and consequences of the impact of remittances of labor migrants on the socioeconomic development of Ukrainian households. Purposelies in identify modern financial indicators that influence the personal decisions regarding remittances of labor migrants for the socio-economic development of the households they receive. Results. It has been determinedthe primary cause of the socioeconomic status of households about regarding the adoption of a decision on labor migration. The positive impact of remittances on the socio-economic behavior of households with labor migrants who make these transfers is determined in paper. There has been carried out a classification of financial factors that affect the movement of money from migrants to their households in Ukraine. It has been systematizedtheinformation on remittances through international payment systems and services of credit and bank institutions in Poland, Russia, the United States and Italy. The differences in the prerequisites of the financial behavior of immigrants are indicated in this paper. Conclusions. The impact of migration processes continues to grow, as under present conditions, migration mobility is one of the elements of the most dynamic process of development of productive forces, which is based on the material provision of households. Along with this, financial relations are developing dynamically, in which labor migrants take an active part. Infrastructure of the same financial market offers affordable services for ensuring the movement and liquidity of household finances. This allowed to distinguish financial indicators of identification and assessment of migratory flows from socio-economic, identify the root causes, evaluate them for the development of households and the state.